Organic cultivation of Allium fistulosum under concentrations of Bordeaux mixture - Rossi, Anderson José Danielsson; Ferreira, Regina Lúcia Félix; Araújo Neto , Sebastião Elviro de; Uchoa, Thays Lemos; Pinto , Geazi Penha; Santos , Alice Gomes de Almeida; Carvalho, Lucas Agueiro de (Comunicata Scientiae, 2024)
Allium fistulosum L., belonging to the botanical family Alliaceae, is one of the most produced and commercialized vegetables in the world. In this scenario, this study aimed to evaluate the control of anthracnose in chives subjected to organic cultivation with different concentrations of Bordeaux mixture and its effects on crop yield. The experiment was conducted in elevated soil beds 10-cm high. Seedlings of the chive cultivar ‘Todo Ano’ were produced from plants previously cultivated in the site. Cultivation was carried out under full sunlight, and irrigation was performed by automatic sprinklers with a daily volume of 6 mm. The experiment was in randomized blocks, with 10 treatments in a 2x5 factorial arrangement. Four concentrations of Bordeaux mixture (0.5%; 1.0%; 1.5%; 2.0%) plus one control (water) were used. The second factor evaluated was the weekly and fortnightly application period. Data on the Total Fresh Mass (MFT), Commercial Fresh Mass (MFC), Sick Fresh Mass (MFR), Number of Commercial Leaves (NFC), Number of Sick Leaves (NFR), Commercial Dry Mass (MSC), and Yield (PTV) were collected. No statistically significant interactions were observed for anthracnose control and chive yield. However, in the 4th week of evaluation, differences were observed between the application periods, with the 2.0% concentration and weekly application performing better than the other treatments. The other evaluations did not result in significant statistical interactions between the variables analyzed. The application of Bordeaux mixture has no effects on the control of anthracnose and on the yield of chives.